2014
DOI: 10.1016/j.apcata.2014.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Ag–Au/SiO2 catalysts: Formation, structure and synergistic activity in glucose oxidation

Abstract: SiO 2 supported Ag-Au bimetallic catalysts were prepared by sol adsorption method with 10/90, 20/80, 33/67, and 50/50 Ag/Au molar ratios. Reduction of HAuCl 4 in Ag sol resulted in alloyed AgAu colloid particles and that structure remained after calcination and reduction treatment. The alloy structure of the catalysts was confirmed by UV-visible spectroscopy and high resolution transmission electron microscopy. The Au-Ag bimetallic effect and its dependence on the Ag/Au molar ratio was studied in glucose oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 62 publications
(61 reference statements)
2
40
0
Order By: Relevance
“…Au-Cu was one of the most investigated bimetallic system with several examples of excellent performance reported both for selective oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylicacid [23], for CO oxidation [24] and CO-PROX [25]. Au-Ag catalysts also received considerable attention in the literature for glucose oxidation [26], CO oxidation [27] and CO-PROX [28].…”
Section: Introductionmentioning
confidence: 98%
“…Au-Cu was one of the most investigated bimetallic system with several examples of excellent performance reported both for selective oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylicacid [23], for CO oxidation [24] and CO-PROX [25]. Au-Ag catalysts also received considerable attention in the literature for glucose oxidation [26], CO oxidation [27] and CO-PROX [28].…”
Section: Introductionmentioning
confidence: 98%
“…[6][7][8] Consequently, it is desirable to explore simple and effective methods to maintain the longterm stability so as to determine the catalytic performance of AgNPs. [17][18][19][20][21] Lu et al reported on the in situ synthesis of AgNPs onto polystyrene (PS) core-poly(acrylic acid) (PAA) polyelectrolyte brush particles. [9][10][11][12] Hybrid catalysts integrated AgNPs with inorganic and organic supports have been successfully developed.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, electron microscopy revealed that the particles in Au-Pd/TiO 2 remained bimetallic after H 2 or after O 2 then H 2 treatment whereas those in Au-Rh/TiO 2 , turned Janus-type after H 2 treatment, and tended to segregate into two separate phases with small Rh particles and larger Au ones after O 2 then H 2 treatment (Figure 4). PVA was also used to stabilize Au-Ag colloids but first with the synthesis of PVA-stabilized Ag to avoid AgCl precipitation then the addition of HAuCl 4 and PVA followed by NaBH 4 [71]. Adsorption of the Au-Ag colloids on TiO 2 was assisted by poly(diallyldimethylammonium) chloride (PDDA) addition.…”
Section: Colloidal Metal Particlesmentioning
confidence: 99%